The Relationship of Premenstrual Syndrome And Obestiy in Adolescence - Yılmaz, Feray Çağıran; Çağıran, Derya (Gümüşhane Üniversitesi, 2023)
With this cross-sectional study, it is aimed to examine the relationship between premenstrual syndrome and obesity in adolescence. This cross-sectional study was conducted with 650 adolescents aged 12-18 years who applied to the Pediatric Adolescent Outpatient Clinic and voluntarily agreed to participate in the study. Anthropometric measurements of the adolescents were taken and the Premenstrual Syndrome Scale was applied. premenstrual syndrome was detected in all of the adolescents participating in the study. It was determined that there was a statistically significant difference between premenstrual syndrome and the body mass index classification of adolescents (p

Bu kesitsel çalışma ile, adolesan dönemde premenstrual sendromun obezite ile ilişkisinin incelenmesi amaçlanmaktadır. Kesitsel olarak yürütülen bu çalışma Çocuk Adolesan Polikliniği’ne başvuran 12-18 yaş grubu araştırmaya katılmayı gönüllü olarak kabul eden 650 adolesan ile yürütülmüştür. Adolesanların antropometrik ölçümleri alınarak, Premenstrual Sendrom Ölçeği uygulanmıştır. Çalışmaya katılan adolesanların tamamında premenstrual sendrom varlığı saptanmıştır. Premenstrual sendrom ile adolesanların beden kütle indeksi sınıflaması arasında istatistiksel olarak anlamlı bir farklılık olduğu belirlenmiştir (p
Adolesan Dönemde Premenstrual Sendromun Obezite İle İlişkisi
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi